MAKNA PUISI HARU NO UTA KARYA SHINPEI KUSANO: KAJIAN SEMIOTIKA RIFFATERRE - Ni Putu Diah Tirta Ningsih; Ni Wayan Meidariani (Janaru Saja Jurnal Program Studi Sastra Jepang, 2025)
Abstract   This study aims to determine the meaning contained in the poem "Haru no Uta" by Shinpei Kusano by using Riffaterre's Semiotics theory. Michael Riffaterre is an expert who develops semiotic theory in the field of the meaning of poetry, this theory is outlined in his book entitled Semiotic of Poetry. The stages of analysis in this theory are (1) heuristic reading, (2) hermeneutic reading with the addition of indirect expressions, (3) searching matrices, models and variants, (4) hypograms. The data source used in this study is a primary data source, namely a poem entitled "Haru no Uta" obtained from a YouTube video "ondoku chaneru". The research method used in this study is a qualitative research method, and uses data collection techniques in the form of listening techniques and library techniques. Based on the stages of analysis, the results found in the poem "Haru no Uta" are that the poem means happiness and joy because it has managed to survive through life's obstacles.   Keywords: Meaning, Poetry, Riffaterre Semiotics   Abstrak   Penelitian ini bertujuan untuk mengetahui makna yang terkandung dalam puisi “Haru no Uta” karya Shinpei Kusano dengan menggunakan teori Semiotika Riffaterre. Michael Riffaterre merupakan seorang ahli yang mengembangkan teori semiotika di bidang makna puisi, teori tersebut dituangkan dalam bukunya yang berjudul Semiotic of Poetry. Tahapan analisis dalam teori tersebut berupa (1) pembacaan heuristik, (2) pembacaan hermeneutik dengan tambahan ketidaklangsungan ekspresi, (3) pencarian matriks, model dan varian, (4) hipogram. Sumber data yang digunakan dalam penelitian ini berupa sumber data primer yaitu berupa sebuah puisi yang berjudul “Haru no Uta” yang diperoleh dari sebuah video youtube “ondoku chaneru”. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kualitatif, serta menggunakan teknik pengumpulan data berupa teknik simak dan teknik pustaka. Berdasarkan tahapan-tahapan analisis, hasil yang ditemukan pada puisi “Haru no Uta” yaitu puisi tersebut bermakna kebahagiaan dan sukacita karena telah berhasil bertahan hidup dalam melewati rintangan hidup.   Kata kunci: Makna, Puisi, Semiotika Riffaterre